Wanprestasi Dalam Perjanjian Makan Hasil Dusun - Irawati Rommer; Teng Berlianty; Sarah Selfina Kuahaty (LUTUR Law Journal, 2023)
There is a shape of agreement to enjoy the results of the community in Kehly Village, Damer Island District, Southwest Maluku Regency, which is commonly known as "eating hamlets" or in the regional language "Rsakar" or "Rsakaro Likut/Ela", where the essence of the agreement is the same as the production sharing agreement. The distribution of the results of the agreement is influenced by factors such as soil fertility, soil availability, provision of seeds, types of crops, and so on. If the land to be managed will be made into a hamlet, and the crops provided by the landowner (the grantor of inheritance), then the proceeds are divided based on the number of heirs entitled to receive the inheritance. This kind of agreement is called "Elab Nuru". This research used normative legal research. The results showed that the agreement written or oral is a valid agreement because it meets the elements of the agreement listed in article 1320 of the Civil Code. Therefore, the parties who make the agreement either orally or in writing are obliged to carry out the obligations according to the agreement, as stipulated in article 1234 of the Civil Code which states that "every engagement aims to give something, do something, or not do something." If one of the parties does not fulfill its obligations, then that party has defaulted.